PENGARUH KUALITAS PRODUK, KEPERCAYAAN, DAN KEPUASAN TERHADAP LOYALITAS UD. DELVI PLANET T-SHIRT CENTRAL PASAR MEDAN - Dewi Maya Sari; Endang Sulistya Rini (Jurnal Media Informasi Manajemen, 2013)
ABSTRACTUD. Delvi Planet T-shirts are located in the Central Pasar is Medan Wholesale trade businesses engaged in the sale of children's clothing and adult. Amid tight fashion business for the children, especially clothing, kids wear business prospects arguably no death, given the clothing is the main requirement. This study aims to identify and analyze the relationship between product quality, trust, loyalty and satisfaction with UD. Delvi Planet T-Shirt Central Pasar Medan.Keywords : Quality products, Confidence, Satisfaction, Customer Loyalty